Aplikasi Media Pembelajaran Mengenal Alat Musik Tradisional Untuk Anak-Anak Berbasis Augmented Reality Pada Perangkat Mobile - Novia, Leli; Zalilludin, Dadan (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
Nowadays technological developments can be used in all aspects from simple to complex work. One of them is as a learning media in getting to know traditional musical instruments. In the field of music, both traditional and modern music, both types of music have different levels of development. Modern music is observed to be progressing faster than traditional music as well as enthusiasts. because modern musical instruments are very easy to find in public places. Augmented reality (AR) application that can combine real world with virtual world in 3D and is interactive in real time, by utilizing Augmented Reality technology that is applied on Android mobile devices. How this application works using the Android smartphone camera as an input for tracking and reading markers (markers) using the tracking system. so users can get to know this traditional musical instrument based on shape. Efforts to increase children's interest in learning Traditional Musical Instruments are continuing. This application is expected to increase the sense of love for traditional musical instruments. also can make it easier to learn traditional musical instruments without having to go where the origin of traditional musical instruments is located. Making an application that will be built using MDLC as a method in developing the system. and blender software as a 3D creation, after the application is built then it can be implemented directly using markers